AMPA GluR-A receptor subunit mediates hippocampal responsiveness in mice exposed to stress - Fumagalli, Fabio; Caffino, Lucia; Vogt, Miriam A.; Frasca, Angelisa; Racagni, Giorgio; Sprengel, Rolf; Gass, Peter; Riva, Marco Andrea (Hippocampus, 2011)
Because stress represents a major precipitating event for psychiatric disorders, it is important to identify molecular mechanisms that may be altered in vulnerable individuals when exposed to stress. Here, we studied GluR-A−/− mice, animals with compromised AMPA receptor signaling, and characterized by a schizophrenic as well as depressive phenotype to investigate changes occurring in response to an acute stress. Wild-type and GluR-A−/− mice were exposed to a single immobilization stress and sacrificed immediately after the end of the stress for the analysis of activity regulated genes and of glutamatergic synapse responsiveness. The acute stress produced a marked increase in the hippocampal expression of Arc (activity-regulated cytoskeletal-associated protein) in GluR-A−/−, but not in wild-type mice, which was associated with a similar increase of phospho-CaMKII, a partner in the action of Arc. When looking at the glutamatergic response to stress in wild-type animals, we found that stress increased GluR-A phosphorylation on serine831, an effect that was paralleled by a significant increase of the phosphorylation of the main NMDA receptor subunits, that is, NR-1 and NR-2B. Conversely, the stress-induced modulation of NMDA receptor subunits was not observed in GluR-A−/− mice. We suggest that enhanced stress responsiveness in GluR-A−/− mice may be due, at least in part, to their inability to activate NMDA-mediated glutamatergic neurotransmission, suggesting that the integrity of AMPA/NMDA receptor function may be important for successful coping under stressful conditions. © 2010 Wiley-Liss, Inc.